SENSOR ACCELEROMETER MMA7361 SEBAGAI DETEKSI GETARAN PADA TANGGUL LUMPUR LAPINDO : MMA7361 ACCELEROMETER SENSOR AS VIBRATION DETECTION ON LAPINDO MUD EMBED - Shazana Dhiya Ayuni; Jamaaluddin; Sy. Syahrorini (Program Studi Teknologi Informasi, 2021)
Lapindo mudflow caused by leakage natural gas drilling in charge by neglation of PT. Lapindo Brantas since 2006. It has been 14 years ago but mudflow still can not be stopped and inflict a financial loss to citizen who lived around the embankment. Eventough the embankment and guardrails were built but sometimes the mud flow into resident’s houses while its raining caused of increases water discharge or the embankment subsidience or reep. In fact, there isn’t any mitigation disaster system from any institution who responbility of this disaster. Whereas the resident’s houses located not far from the embankment, around 500 m away.That happens usually is the mudflow is already stagnate at their house it will took for more days to reconstruction the embankment. therefore it will be more efficiently if we monitoring the embankment vibration using accelerometer sensor where located in dike-prone points then it send via smartphone using Blynk application. Every vibration will show real time at Blynk, so the citizen can monitoring security of this Lapindo embankment. When the accident happened the application will send warning and notification to smartphone so they can save their live and property.